Five-year technology selection optimization to achieve specific CO2 emission reduction targets. (5th February 2019) - Shamsi, Hamidreza; Haghi, Ehsan; Raahemifar, Kaamran; Fowler, Michael
Abstract: Long-term planning for replacement of fossil fuel energy technologies with renewables is of great importance for achieving GHG emission reduction targets. The current study is focused on developing a five-year mathematical model for finding the optimal sizing of renewable energy technologies for achieving certain CO2 emission reduction targets. A manufacturing industrial facility which uses CHP for electricity generation and natural gas for heating is considered as the base case in this work. Different renewable energy technologies are developed each year to achieve a 4.53% annual CO2 emission reduction target. The results of this study show that wind power is the most cost-effective technology for reducing emissions in the first and second year with a cost of 44 and 69 CAD per tonne of CO2, respectively. Hydrogen, on the other hand, is more cost-effective than wind power in reducing CO2 emissions from the third year on. The cost of CO2 emission reduction with hydrogen doesn't change drastically from the first year to the fifth year (107 and 130 CAD per tonne of CO2 ). Solar power is a more expensive technology than wind power for reducing CO2 emissions in all years due to lower capacity factor (in Ontario), more intermittency (requiring mores storage capacity), and higher investment cost. A hybrid wind/battery/hydrogen energy system has the lowest emission reduction cost over five years. The emission reduction cost of such hybrid system increases from 44 CAD per tonne of CO2 in the first year to 156 CAD per tonne of CO2 in the fifth year. The developed model can be used for long-term planning of energy systems for achieving GHG emission targets in a regions/country which has fossil fuel-based electricity and heat generation infrastructure. Highlights: A five-year technology selection optimization model is developed. Wind power is a cost-efficient technology for reducing emissions in the first years. Hydrogen is more cost-effective than wind power from the third year on. The cost of emission reduction with hydrogen doesn't change drastically in five years. Hybrid wind/battery/hydrogen system has the lowest emission reduction cost overall.